The Moderating Effect of Income Diversification on Intellectual Capital and Company Performance in Indonesian Banking - Wahyuningtias, Eko; Sari, Pristin Prima; Kusumawardhani, Ratih (Jurnal Keuangan dan Perbankan, 2023)
This research aims to examine the influence of intellectual capital on company performance, the moderating effect of revenue diversification, and provide additional insight into intellectual capital. This research uses 38 banks in Indonesia that are listed on the Indonesia Stock Exchange (BEI) out of a total of 47 banks as research samples. The collected data was analyzed using linear regression and moderated regression analyses to test the effect of intellectual capital on company performance and the moderating impact of income diversification on intellectual capital and company performance. The results of the regression analysis show that intellectual capital (VAIC) has a positive effect on company performance. In contrast, income diversification is having a moderating impact on intellectual capital and company performance. The intellectual capital component has varying influences on company performance. Whereas VACA positively affects company performance, VAHU also positively impacts company performance. At the same time, STVA does not affect company performance. Based on the moderation test, income diversification does not moderate the relationship between intellectual capital components and company performance.DOI: 10.26905/jkdp.v27i3.11449